Evaluation Of Patient’s Satisfaction Towards Pharmaceutical Services At Outpatient Installation In Putra Wasada Hospital Tulungagung - Restyana, Anggi; Viky Yustriana; Wika Admaja (Journal of Hospital Management and Services, 2024)
Pharmaceutical service is a direct and responsible service to patients related to pharmaceutical preparations with the aim of improving the quality of life of patients. Patient satisfaction is the first indicator of a hospital's standards and is a measure of service quality. The purpose of this study was to determine the level of satisfaction based on 5 dimensions of pharmaceutical services in the Outpatient pharmacy installation of Putra Waspada Hospital Tulungagung using the ServQual method. This research was a descriptive research using random sampling design. This research was conducted prospectively with quantitative method using data collection method, namely the ServQual method and the Chi-square test method carried out using questionnaires. There were 225 of samples of patient respondents, to determine the characteristics of respondents and the influences between respondent characteristics and the level of patient satisfaction on 5 dimensions of pharmaceutical services at the Outpatient Pharmacy Installation of Putra Waspada Hospital Tulungagung using the Chi-square test. Based on the result of the percentage of the patient satisfaction level at the performance level stated that 56 respondents (56%) stated "very satisfied" with pharmaceutical services, while 41 respondents (41%) stated "satisfied", at the expectation level 55 respondents (55%) stated "very satisfied", 42 respondents (42%) stated "satisfied". Based on ServQual's analysis, patient satisfaction scores on 5 dimensions of pharmaceutical services have a "fair" interpretation with a satisfaction level of "satisfied" and have a high interpretation with a satisfaction level of "very satisfied". In outpatients with each dimension of 0.90 (reliability), 0.96 (responsiveness), 0.98 (asssurance), 0.92 (empathy), 0.93 (physical infrastructure).